Academic and Social Engagement: The Effect of Flipped Classroom on Physical Fitness by Using Teaching Game for Understanding Strategy - Syamsuar, Syamsuar; Zen, Zelhendri; Reflianto, Reflianto (Indonesian Journal of Instructional Media and Model, 2023)
The research aimed to analyze the implementation of flipped classrooms with the Teaching Game of Understanding Strategy in Sports Teaching to strengthen students’ Academic and social engagement in improving Physical Fitness in playing volleyball. This study used experimental-quantitative research with survey methods. The sample of this study is fifth-grade students of Fifth-grade of Elementary School of Sungai Sariak 11 Padang Pariaman as many as 40 people. Students’ academic and social engagement data were collected by using questionnaires with a 5-point Likert scale and physical fitness data were collected by using Indonesian Physical Fitness Test. The data analysis used multiple linear regression tests. Research findings reported that the implementation of the Teaching Game of Understanding to strengthen students’ Academic and social engagement in improving students’ Physical Fitness in playing volleyball in the line of socialization; personality and self-control have significant relation with students’ physical fitness and Academic engagement also showed significant relation with students’ physical fitness covered to PUC, TIR, EVN and LMR group. Sports teachers can utilize the Teaching Game of Understanding model to volleyball learners improve their physical fitness.